Association between muscle power impairment and WHODAS 2.0 in older adults with physical disability in Taiwan. (15th July 2014) - Chang, Kwang-Hwa; Liao, Hua-Fang; Yen, Chia-Fan; Hwang, Ai-Wen; Chi, Wen-Chou; Escorpizo, Reuben; Liou, Tsan-Hon
Abstract: Purpose : To explore the association between muscle power impairment and each World Health Organization Disability Assessment Schedule second edition (WHODAS 2.0) domain score among subjects with physical disability. Methods : Subjects (≥60 years) with physical disability related to neurological diseases, including 730 subjects with brain disease (BD) and 126 subjects with non-BD, were enrolled from a data bank of persons with disabilities from 1 July 2011 to 29 February 2012. Standardized WHODAS 2.0 scores ranging from 0 (least difficulty) to 100 (greatest difficulty) points were calculated for each domain. Results : More than 50% of subjects with physical disability had the greatest difficulty in household activities and mobility . Muscle power impairment (adjusted odds ratios range among domains, 2.75–376.42, p  < 0.001), age (1.38–4.81, p  < 0.05), and speech impairment (1.94–5.80, p  < 0.05) were associated with BD subjects experiencing the greatest difficulty in most WHODAS 2.0 domains. But a few associated factors were identified for the non-BD group in the study. Conclusions : Although the patterns of difficulty in most daily activities were similar between the BD and non-BD groups, factors associated with the difficulties differed between those two groups. Muscle power impairment, age and speech impairment were important factors associated with difficulties in subjects with BD-related physical disability. Implications for Rehabilitation: Older adults with physical disability often experience difficulties in household activities and mobility . Muscle power impairment is associated with difficulties in daily life in subjects with physical disability related to brain disease. Those subjects with brain disease who had older age, a greater degree of muscle power impairment, and the presence of speech impairment were at higher risk of experiencing difficulties in most daily activities.